Phenolic Compound Content of a Plant of the Genus Vigna From Chad : Vigna Unguiculata (Fabaceae) - Abel, MBAIOGAOU; Severin, MBAIHOUGADOBE; Salmon, MADJITOLOUM BETOLOUM; Michel, NAITORMBAIDE; DJADDA, Mouta Adji (British Journal of Healthcare and Medical Research, 2022)
Nine (09) varieties of Vigna unguiculata provided by the CIARD of Bebedja city in Chad were studied for their antioxidant activities and their contents in total polyphenols, total anthocyanins and total flavonoids. The measurement of the antioxidant capacity of the total extracts was estimated by the DPPH test. The contents of total polyphenols, total flavonoids and total anthocyanins in the seed extracts were determined by the Folin Ciocalteu, aluminum trichloride (AlCl3) and pH-differential methods respectively. From this study, three (3) varieties rich in antioxidants were found: NDJAM-2, TN5-78 and NDJAM-1 with respective contents of 3.14 mg QE/g, 3.113 mg QE/g and 3.07 mg QE/g of dry seeds. These varieties were also rich in total polyphenols with contents of 4.457 mg GAE/g, 4.095 mg GAE/g and 3.875 mg GAE/g of dry seeds respectively. The varieties TN5-78, VYA, IT99K573-1-1 are the best in total flavonoids with values of 0.744 mg QE/g, 0.712 mg QE/g and 0.579 mg QE/g of dry seeds respectively. Total anthocyanins are generally low in most varieties except TN5-78 and N'DJAM-2 which have 0.161 mg/g and 0.133 mg/g respectively.